Pelatihan Penggunaan Program R Untuk Meningkatkan Kompetensi Olah Data Statistik Bagi Guru Biologi SMA - Irwan Lovadi; Rafdinal Rafdinal; Siti Ifadatin; Firman Saputra; Dwi Gusmalawati; Junardi Junardi (I-Com: Indonesian Community Journal, 2024)
Improving teachers' competence is one of the objectives of the subject teachers' group (MGMP). One important competency that teachers is the ability to publish scientific papers. Statistical data analysis and data visualisation are important components in scientific publications, but these two things are challenging. This program aims to improve the knowledge and skills of teachers who are members of MGMP Biology SMA in Pontianak, in statistical data analysis and data visualisation through training in the use of R and RStudio (Posit). In this course, we delivered presentations and demonstration of the use of R and RStudio. At the end of demonstration activities, each participant carried out independent completion of the use of R and RStudio. This training activity was attended by 16 participants from several high schools in Pontianak. The results showed that there was an increase in the knowledge and skills of the participants based on the results of the pre-test and post-test assessments.